2015
DOI: 10.1242/jeb.114876
|View full text |Cite
|
Sign up to set email alerts
|

Sequential exposure to a combination of stressors blocks memory reconsolidation in Lymnaea

Abstract: Stress alters the formation of long-term memory (LTM) in Lymnaea. When snails are exposed to more than one stressor, however, how the memory is altered becomes complicated. Here, we investigated how multiple stressors applied in a specific pattern affect an aspect of memory not often studied in regards to stress -reconsolidation. We hypothesized that the application of a sequence of stressors would block the reconsolidation process. Reconsolidation occurs following activation of a previously formed memory. Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…We have described the data that confirm the existence of a contextual memory in mollusks, which has been shown by us previously (Gainutdinova et al, 2004 ; Balaban et al, 2014 ) and other researchers (Child et al, 2003 ; Kemenes et al, 2006 ; Lukowiak et al, 2007 ; Solntseva et al, 2007 ; Cai et al, 2012 ; Nikitin and Solntseva, 2012 ; Dodd and Lukowiak, 2015 ; Balaban et al, 2016 ). The experimental results showed that memory reactivation (after reminder) 2 days after learning in our previous studies (Gainutdinova et al, 2005 ; Balaban et al, 2014 ) and 5 days after learning in present was a process that sensitive to inhibition of protein synthesis, included in either memory storage or its expression.…”
Section: Resultssupporting
confidence: 80%
“…We have described the data that confirm the existence of a contextual memory in mollusks, which has been shown by us previously (Gainutdinova et al, 2004 ; Balaban et al, 2014 ) and other researchers (Child et al, 2003 ; Kemenes et al, 2006 ; Lukowiak et al, 2007 ; Solntseva et al, 2007 ; Cai et al, 2012 ; Nikitin and Solntseva, 2012 ; Dodd and Lukowiak, 2015 ; Balaban et al, 2016 ). The experimental results showed that memory reactivation (after reminder) 2 days after learning in our previous studies (Gainutdinova et al, 2005 ; Balaban et al, 2014 ) and 5 days after learning in present was a process that sensitive to inhibition of protein synthesis, included in either memory storage or its expression.…”
Section: Resultssupporting
confidence: 80%
“…Early and recent non-human animals studies show that both stressful experiences or glucocorticoids administration before or during reconsolidation can affect subsequent memory retention in both directions (Bustos, Giachero, Maldonado, and Molina, 2010;Cai, Blundell, Han, Greene, and Powell, 2006;Dodd and Lukowiak, 2015;Frenkel et al, 2005;Frenkel et al, 2010;Merz, Wolf, and Hennig, 2010;Tronel and Alberini, 2007). In agreement, studies in humans using diverse memory paradigms with different emotional contents show that stressors after memory reactivation, or during reconsolidation, can enhance or impair memory (Agren, 2014;Bos, Jacobs van Goethem, Beckers, and Kindt, 2014;Bos, Schuijer, Lodestijn, Beckers, and Kindt, 2014;Cheung, Garber, and Bryant, 2015;Hupbach and Dorskind, 2014;Kindt and van Emmerik, 2016;Merlo, Bekinschtein, Jonkman, and Medina, 2015;Nader, Hardt, and Lanius, 2013;Schwabe, Nader, and Pruessner, 2014;Schwabe and Wolf, 2009;2010).…”
Section: Stress and Reconsolidation: Positive And Negative Memory Effmentioning
confidence: 76%
“…Does the modulatory effect of stress depend on intensity levels? Dodd and Lukowiak (2015) trained snails in an operant conditioning paradigm of aerial respiratory behavior. When this operant memory was reactivated and followed by multiple stressors (both handling and crowding), the snails’ performance was impaired, presumably due to reconsolidation disruption.…”
Section: Behavioral Manipulation Of Reconsolidationmentioning
confidence: 99%
“…), has to be further investigated.Can stress be implemented in future therapeutic reconsolidation-based interventions? Stress timing in relation to retrieval can be easily modified in treatment, but if intense stress is required for it to create a significant interruption to the reactivated memory (Dodd & Lukowiak, 2015), it is not ideal for therapy. However, even mild stressors can be successfully used for the disruption of emotional memory reconsolidation (Zhao et al, 2009) in humans.…”
Section: Behavioral Manipulation Of Reconsolidationmentioning
confidence: 99%